Promoting irrigation demand management in India: options, linkages and strategy - Saleth, Rathinasamy Maria; Amarasinghe, Upali A. (IWA Publishing, 2010)
Against the backdrop of a discussion on the rationale, logic and scope of irrigation demand management in India, this paper provides a brief overview of the status, effectiveness and technical and institutional requirements of six demand management options, that is, water pricing, water markets, water rights, energy regulations, water saving technologies and user organizations. The paper then develops a framework that captures the analytics of irrigation demand management in terms of both the impact pathways of and the operational linkages between the options and their underlying institutions. Using this framework, the paper also outlines a strategy for irrigation demand management that can exploit the inherent synergies between the options and align them well with the underlying institutional structure and its environment. After discussing how such a strategy can be effectively promoted within the institutional and political constraints facing countries such as India, the paper concludes with the policy implications of irrigation demand management.